Climate Change and legal responsibility - Bonorino Ramírez, P. R. (2021)
Climate change will damage a scale difficult to measure. Its magnitude and peculiarity may lead us to reconsider how we understand some fundamental legal and moral concepts. In this paper the concept of legal responsibility is analyzed, trying to determine what would be the changes that should operate in their traditional use to deal with situations that can lead to global climate change in the coming decades. To do this we will make a general reflection on the limits and foundations of legal responsibility, analyzing the subjective or personal responsibility, and establishing the conditions that could accept collective legal liability for damages that could generate climate change. Finally we reflect on the feasibility of considering as the main contributor to climate change the capitalist mode of production and political alternatives that are available to mitigate their effects.